Longitudinal Validity and Minimal Important Change for the Modified Lower Extremity Functional Scale (LEFS) in Orthopedic Foot and Ankle Patients - Saarinen Antti J.; Bondfork Anton S; Repo Jussi; Sandelin Henrik; Uimonen Mikko (Elsevier, 2022)
The lower extremity functional scale (LEFS) is a patient-reported outcome measure for lower extremity disorders. Aim of this study was to assess the longitudinal validity including responsiveness and test-retest reliability of the revised 15-item version, and to define the minimal important change (MIC) of the modified LEFS in a generic sample of orthopedic foot and ankle patients who underwent surgery. Responsiveness, effect size, and standardized response mean were measured by determining the score change between the baseline and 6 months administration of the LEFS from 156 patients. There was no significant difference between preoperative (median 78, interquartile range [IQR] 64.2-90.3) and postoperative (median 75.0, IQR 61.7-95.0) scores. Both effect size and standardized response mean were low (0.06 and 0.06, respectively). Test-retest reliability of the LEFS was satisfactory. Intraclass correlation coefficient was 0.85 (95% confidence interval 0.81-0.88). MIC value could not be estimated due to the lack of significant score change. The modified LEFS presented with relatively low longitudinal validity in a cohort of generic orthopedic foot and ankle patients. The findings of this study indicate that the modified LEFS might not be the optimal instrument in assessing the clinical change over time for these patients.